Longitudinal changes in each retinal layer thickness in patients with moderate or more severe diabetic retinopathy taking calcium dobesilate - Jung-Tae Kim; Min-Woo Lee (PLoS ONE, 2025)
Purpose To longitudinally analyze the impact of calcium dobesilate (CaD) treatment on retinal layer thicknesses in patients with moderate or more severe diabetic retinopathy (DR). Methods In this retrospective, longitudinal study, patients with DR exhibiting moderate non-proliferative diabetic retinopathy (NPDR) or more advanced stages were enrolled and divided into two groups: those prescribed CaD for more than 6 months (Group 1) and those not prescribed CaD (Group 2). After the baseline visits, three additional examinations were conducted at 1-year intervals. Results In total, 128 eyes were included: 38 in Group 1 and 90 in Group 2. Over time, group 2 exhibited significant decreases in ganglion cell complex (GCC) and inner nuclear layer (INL) thicknesses (P < 0.001 and P = 0.002, respectively), while Group 1 did not. Both groups experienced significant reductions in outer nuclear layer (ONL) thickness (P = 0.030 for Group 1 and P < 0.001 for Group 2). Group 2 exhibited a significantly greater decrease in GCC thickness compared with Group 1(P = 0.026). Conclusions In patients with moderate or more severe DR, the group taking CaD did not show significant reductions in GCC and INL thicknesses over time compared with the group not taking CaD. These findings suggest that CaD could have a protective effect on the inner retina, even in those with more advanced stages than mild DR.